Ezra, Nehemiah and Esther - Brockington, L.H. (London, UK Thomas Nelson and Sons, 1969)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Ezra -- commentaries; Bible. O.T. Nehemiah -- commentaries; Bible. O.T. Esther -- commentaries